"Van de Utrechtsche Socialisten-Meeting tegen het ontwerp-Landstormwet". Uit: De Amsterdammer, 4-7-'15 - Collette, Joan
"Van de Utrechtsche Socialisten-Meeting tegen het ontwerp-Landstormwet". Uit: De Amsterdammer, 4-7-'15.